Anxiety in language teachers: Exploring the variety of perceptions with Q methodology - Fraschini, Nicola; Park, Hyunjin (Foreign language annals, 2021)
The negative effects of anxiety on teachers' lives, classroom practice, and student learning have highlighted the importance of this emotion for the language teaching field. An understanding of anxiety in language teaching offers a means to explore how language teachers interact with their professional environment, also yielding important implications for teacher well‐being. This paper uses Q methodology to investigate Korean as a second language teachers' shared experiences related to anxiety in the language teaching profession, foregrounding different ways that language teachers interact with their professional environment, and exploring holistically participants' subjectivities. Results identified the presence of three major perspectives, representing types of teachers' individual responses to the interaction between their personal and professional goals and their working context—(1) work/life balance, (2) job performance and evaluation, (3) job security. Implications of the results are discussed in relation to research on classroom emotions and language institution practices. The Challenge Anxiety is a negative emotion affecting teachers' professional lives and student learning outcomes; however, research on language teacher anxiety is scant. What are the implications of the tension between personal goals and the professional environment in a language teaching context? This paper examines shared experiences of Korean language teachers.